Tanzania - River Basin Management and Smallholder Irrigation Project - Mohan, P.C. (World Bank, Washington, DC, 2012)
Tanzania's ability to manage scarce water resources became a national issue in the early to mid-1990s. New opportunities in agriculture, and the greater demand for water for irrigation and hydropower, together with the long dry season and several years of less-than-average rainfall, contributed to water scarcity and conflicts, while the lack of information on water quantity and quality, and an inadequate framework for tackling cross-sectoral water issues severely constrained sustainable water resource management. Tanzania has defined nine river basins for water resources administration. The project components included River Basin Management, and Smallholder Irrigation Improvement and this paper examines impact on the ground and lessons learned from the project.